The Effect of E-WOM on Social Media on Consumers' Interest in Buying Compass Shoes Using an Information Adoption Approach - Abi Hasan Sajali (Institute of Computer Science (IOCS), 2022)
This study aims to analyze the influence of E-WOM on social media on consumers' interest in and buying interest in Compass shoes with an information adoption approach. Quantitative research design. This study's population is all consumers familiar with Compass shoes and consumers who already have Compass shoes in various cities. Sampling employing a technique of purposive sampling, with the number of samples reaching 300 respondents. Data collection utilizing questionnaires validated for validity and reliability, and data processing using AMOS with a 95% degree of assurance (p 0.05). The results indicated that the quality of information has a significant positive effect on the usefulness of information (p = 0.005); the credibility of information has a positive effect on the use of information (p = 0.000); the need for information has a positive effect on the usefulness of information (p = 0.000); the need for information has a positive effect on the adoption of information (p = 0.000); and the attitude toward information has a positive effect on interest (p = 0.001). Moreover, the adoption of knowledge affects purchasing intent positively (p = 0.000). Therefore, the entire hypothesis was validated, and the conclusion is that E-WOM has a substantial impact on consumer interest in purchasing Compass shoes via social media.